A Low‐Strain Phosphate Cathode for High‐Rate and Ultralong Cycle‐Life Potassium‐Ion Batteries. (22nd October 2021) - Liao, Jiaying; Chen, Cailing; Hu, Qiao; Du, Yichen; He, Yanan; Xu, Yifan; Zhang, Zhuangzhuang; Zhou, Xiaosi
Abstract: Most potassium‐ion battery (PIB) cathode materials have deficient structural stability because of the huge radius of potassium ion, leading to inferior cycling performance. We report the controllable synthesis of a novel low‐strain phosphate material K3 (VO)(HV2 O3 )(PO4 )2 (HPO4 ) (denoted KVP) nanorulers as an efficient cathode for PIBs. The as‐synthesized KVP nanoruler cathode exhibits an initial reversible capacity of 80.6 mAh g −1 under 20 mA g −1, with a large average working potential of 4.11 V. It also manifests an excellent rate property of 54.4 mAh g −1 under 5 A g −1, with a high capacity preservation of 92.1 % over 2500 cycles. The outstanding potassium storage capability of KVP nanoruler cathode originates from a low‐strain K + uptake/removal mechanism, inherent semiconductor characteristic, and small K + migration energy barrier. The high energy density and prolonged cyclic stability of KVP nanorulers//polyaniline‐intercalated layered titanate full battery verifies the superiority of KVP nanoruler cathode in PIBs. Abstract : A low‐strain phosphate cathode material K3 (VO)(HV2 O3 )(PO4 )2 (HPO4 ) (KVP) nanoruler is synthesized by a facile solvothermal approach. The KVP nanorulers manifest high discharge voltage, superior rate capability, and ultralong cyclic life as a cathode material for potassium‐ion batteries (PIBs). This work would provide guidance to exploit high‐performance PIB cathode materials.